Kontribusi Pemberdayaan UMKM Terhadap Pembangunan Ekonomi Daerah dan Penyerapan Tenaga Kerja (Kuantitatif) - Gustina Masitoh; Thamara Idil Fitri Marliana; Angga Pratama; Chika Dwi Oktavianai; Feri Kurniawan (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This research aims to examine the role of empowering Micro, Small, and Medium Enterprises (MSMEs) in driving regional economic development while increasing workforce absorption. This topic is relevant considering the crucial position of MSMEs as the driving force of the local economy and the main source of job creation, although in practice they are still limited by limited internal capacity and access to various resources. This study applies a qualitative approach with a case study design to explore in depth the dynamics, processes, and meaning of MSME empowerment in the local context. Data collection was conducted through semi-structured interviews, limited observations, and documentation reviews with five informants including MSME actors, MSME facilitators, and local government representatives. Informants were determined using purposive and snowball sampling techniques. Furthermore, the data were analyzed thematically using the interactive analysis model of Miles and Huberman. The research findings indicate that MSME empowerment efforts through training programs, mentoring, capital facilitation, and marketing support, including digitalization, have significantly contributed to increasing business capacity, expanding market reach, and sustaining business activities. This capacity building has direct implications for opening up local employment opportunities and strengthening a more inclusive regional economic structure. These results add to the theoretical understanding of MSME empowerment from a local economic development perspective, while also offering practical and policy implications for the formulation of sustainability-oriented MSME empowerment programs. Future research is recommended to cover a broader study area and incorporate a mixed-methods approach to increase the generalizability of the findings.